DAMPAK KEBIJAKAN BIODIESEL 20 TERHADAP DAYA SAING EKSPOR MINYAK SAWIT MURNI (CPO) INDONESIA - Pangaribowo, Winantu; Amir, Indra Tjahaja; Sudiyarto, Sudiyarto (Agridevina : Berkala Ilmiah Agribisnis, 2021)
Oil palm is the flagship commodity in Indonesia, the commodity is the biggest foreign exchange contributor for the non-oil sector. This makes Indonesia the world's leading producer and exporter. However, over time there has been a decline in the number of exports of crude palm oil (CPO) Indonesia which caused the government to issue a mandatory biodiesel 20 (B20) policy. The objectives of the study are: 1) identifying the production, price, and export of crude palm oil (CPO) and Indonesian biodiesel, 2) Analyzing the impact of Biodiesel 20 (B20) policy on biodiesel production in Indonesia, 3) Analyzing the competitiveness of Indonesian crude palm oil products (CPO). The methods used are Mann-Whitney U test, Relative Trade Advantage (RTA), Trade Specialisation Index (TSI), and Export Product Dynamics (EPD). The results showed that: 1) an increase in CPO and Biodiesel production; domestic CPO prices and biodiesel prices; and biodiesel exports. Meanwhile, there is a decline in world CPO prices and Indonesian CPO exports. 2) B20 policy affects to CPO production, biodiesel production and biodiesel export. However, no impact on Indonesia's CPO exports. 3) Indonesia still has an advantage in CPO trading in terms of comparative and competitive advantages in DOI : https://doi.org/10.33005/adv.v10i2.2909